Distinct MRI pattern of "pseudoresponse" in recurrent glioblastoma multiforme treated with regorafenib: Case report and literature review. Issue 8 (21st August 2021) - Gatto, Lidia; Franceschi, Enrico; Tosoni, Alicia; Di Nunno, Vincenzo; Maggio, Ilaria; Tonon, Caterina; Lodi, Raffaele; Agati, Raffaele; Bartolini, Stefania; Brandes, Alba Ariela
Abstract: Antiangiogenic agents can induce a distinct MRI pattern in glioblastoma, characterized by a decrease in the contrast enhancement on T1‐weighted images and a simultaneous hyperintensity on T2‐weighted or fluid‐attenuated inversion recovery images. Abstract : Antiangiogenic agents can induce a distinct MRI pattern in glioblastoma, characterized by a decrease in the contrast enhancement on T1‐weighted images and a simultaneous hyperintensity on T2‐weighted or fluid‐attenuated inversion recovery images.